2020
DOI: 10.1093/eurheartj/ehaa612
|View full text |Cite|
|
Sign up to set email alerts
|

2020 ESC Guidelines for the diagnosis and management of atrial fibrillation developed in collaboration with the European Association for Cardio-Thoracic Surgery (EACTS)

Abstract: The content of these European Society of Cardiology (ESC) Guidelines has been published for personal and educational use only. No commercial use is authorized. No part of the ESC Guidelines may be translated or reproduced in any form without written permission from the ESC. Permission can be obtained upon submission of a written request to Oxford University Press, the publisher of the European Heart Journal and the party authorized to handle such permissions on behalf of the ESC (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
2,883
6
371

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 7,072 publications
(3,300 citation statements)
references
References 1,460 publications
40
2,883
6
371
Order By: Relevance
“…Although there is evidence that standardized anticoagulation therapy can significantly improve the prognosis of patients with high risk of thromboembolic events, in fact, most patients with atrial fibrillation do not use anticoagulation therapy. Strategies for identifying patients at risk for thromboembolism are commonly based on the basis of the CHA2DS2 -VASc score (6), however study found biomarkers could further refine stroke risk differentiation among patients initially classified as low risk (7). Clinically, we also found patients with low CHA2DS2 -VASc score still have a risk of thromboembolic events, more valuable forecast indicators of biomarkers in patients with AF seems to be necessary.…”
Section: Introductionmentioning
confidence: 69%
“…Although there is evidence that standardized anticoagulation therapy can significantly improve the prognosis of patients with high risk of thromboembolic events, in fact, most patients with atrial fibrillation do not use anticoagulation therapy. Strategies for identifying patients at risk for thromboembolism are commonly based on the basis of the CHA2DS2 -VASc score (6), however study found biomarkers could further refine stroke risk differentiation among patients initially classified as low risk (7). Clinically, we also found patients with low CHA2DS2 -VASc score still have a risk of thromboembolic events, more valuable forecast indicators of biomarkers in patients with AF seems to be necessary.…”
Section: Introductionmentioning
confidence: 69%
“…This paradigm-shifting therapeutic strategy is most recently validated by the Early Treatment of Atrial Fibrillation for Stroke Prevention Trial (EAST-AFNET 4), an international, randomized, open, blinded-outcome-assessment clinical trial (Kirchhof et al, 2020). In fact, the most recently published 2020 AF guidelines mark a revolutionizing paradigm shift in management strategies because the pressing need for primary prevention to thwart AF atriomyopathy onset is emphasized for the first time (Hindricks et al, 2020).…”
Section: Natural Historymentioning
confidence: 99%
“…В таких случаях диагностический поиск должен быть продолжен с использованием многосуточного ХМ ЭКГ или носимого «регистратора событий». Это досадное недоразумение, затрудняющее практическую работу кардиологов и терапевтов, устранено в совсем недавно появившихся рекомендациях ЕОК 2020 г [4]. Из них следует, что «…диагностическим признаком клинически значимой ФП является отсутствие закономерного повторения зубцов Р и наличие нерегулярных интервалов RR (если АВ проводимость не нарушена), зафиксированные при стандартной записи ЭКГ в 12-ти отведениях или регистрации ЭКГ в одном отведении продолжительностью ≥ 30 секунд».…”
Section: при наличии жалоб на эпизоды неритмичного сердцебиения и приunclassified